Prospects for plant defence activators and biocontrol in IPM – Concepts and lessons learnt so far. (July 2017) - Bruce, Toby J.A.; Smart, Lesley E.; Birch, A. Nicholas E.; Blok, Vivian C.; MacKenzie, Katrin; Guerrieri, Emilio; Cascone, Pasquale; Luna, Estrella; Ton, Jurriaan
Abstract: There is an urgent need to develop new interventions to manage pests because evolution of pesticide resistance and changes in legislation are limiting conventional control options for farmers. We investigated β-aminobutyric acid (BABA), jasmonic acid (JA) and fructose as possible plant defence activators against grey mould disease, Botrytis cinerea, and root knot nematode, Meloidogyne incognita. We also tested Trichogramma achaeae parasitoid wasps and an antifeedant plant extract for biocontrol of the invasive tomato leafminer, Tuta absoluta . BABA and JA enhanced resistance of tomato plants to B. cinerea but neither treatment provided complete protection and the efficacy of treatment varied over time with BABA being more durable than JA. Efficacy was partly dependent on tomato cultivar, with some cultivars responding better to BABA treatment than others. Furthermore, treatment of tomato with BABA, JA and fructose led to partial suppression of M. incognita egg mass development. Biocontrol agent, T. achaeae, performance against T. absoluta could be enhanced by adjusting the rearing conditions. Both attack rate and longevity were improved by rearing the parasitoids on T. absoluta rather than on other insects. Finally, Ajuga chamaepitys extract was shown to have significant antifeedant activity against T. absoluta . Our findings suggest that there are potential new solutions for protection of crops but they are more complicated to deploy, more variable and require more biological knowledge than conventional pesticides. In isolation, they may not provide the same level of protection as pesticides but are likely to be more potent when deployed in combination in IPM strategies. Graphical abstract: How to help plants defend themselves! Highlights: New solutions for managing pests are urgently needed. Plant defence activators can reduce disease and pest pressure. Biocontrol agents can be optimised by rearing under appropriate conditions. Antifeedants can reduce pest damage. A combination of IPM approaches is the most resilient solution.